Implementation of Performance-Based Financing Management in Improving the Management Efficiency of Islamic Junior High School - Anita, Anita; Patimah, Siti; Murtafiah, Nurul Hidayati (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
This study aims to analyze the implementation of performance-based financing and its impact on the efficiency of madrasah management. The research employed a qualitative case study design conducted at MTs Al Ishlah Sukadamai Natar. This approach was chosen to gain an in-depth understanding of the processes, strategies, and dynamics involved in implementing performance-based financing within the real context of an Islamic educational institution. The research subjects included the madrasah principal, treasurer, head of the madrasah committee, and teachers directly involved in the planning and implementation of financing programs, selected through purposive sampling. Data were collected through in-depth interviews, participatory observation, and document analysis, including the Madrasah Work and Budget Plan (MWBB), budget realization reports, meeting minutes, and program evaluation documents. Data analysis followed the interactive model of Miles and Huberman, consisting of data reduction, data display, and inductive conclusion drawing. Data validity was ensured through source and technique triangulation and member checking. The findings indicate that integrating priority performance indicators into planning and budgeting has led to more targeted, efficient spending patterns with direct impacts on the improvement of educational services. Budget allocations were primarily directed toward teacher professional development, the development of digital learning media, and the preventive maintenance of facilities. Despite limited data literacy and inadequate digital infrastructure, the implementation of performance-based financing has enhanced financial efficiency, transparency, and accountability in madrasah financial management. This study concludes that performance-based financing is a relevant and replicable model for promoting professional and sustainable madrasah governance.